Iranian Revolution : A Profile - Waheed-uz-Zaman (Rawalpindi Pap-Board, 1985)
The Iranian people despised their leader, Reza Shah, who catered to foreign businesses while ruling Iran as a dictator. In 1979 discontent boiled up into all-out revolution. Led by the charismatic Ayatollah Khomeini, the Iranian people seized control and created a new government based on the Islamic religion.
Include Notes, Index and Bibliography.
Keywords: Revolution (Iran : 1979) -- Khomeini, Ruhollah